Marine phage genomics: the tip of the iceberg - Perez Sepulveda, Blanca (FEMS Microbiol Lett, 2016)
Marine viruses are the most abundant biological entity in the oceans, the majority of which infect bacteria and are known as bacteriophages. Yet, the bulk of bacteriophages form part of the vast uncultured dark matter of the microbial biosphere. In spite of the paucity of cultured marine bacteriophages, it is known that marine bacteriophages have major impacts on microbial population structure and the biogeochemical cycling of key elements. Despite the ecological relevance of marine bacteriophages, there are relatively few isolates with complete genome sequences. This minireview focuses on knowledge gathered from these genomes put in the context of viral metagenomic data and highlights key advances in the field, particularly focusing on genome structure and auxiliary metabolic genes.